Ion‐Transport Experiments to Probe the Nanostructure of Graphene/Polymer Membranes. Issue 10 (25th July 2018) - Zhang, Mengyang; Cheng, Chi; Simon, George P.; Li, Dan
Abstract: Graphene/polymer layered nanocomposites are studied extensively for their unique two‐dimensional (2D) layered nanoporous structures and interesting permeation properties with regard to ionic species, and show great potential for applications in many fields. Structural characterization is essential to the establishment of structure–properties relationships, which however remains challenging due to the complex, nanoporous texture rising from graphene alignment in graphene/polymer membrane materials. Here, a method is proposed that utilizes ions as probes for gaining structural information of the layered nanoporous structure. The results show that the subtle structural variations caused by the small change of interfacial interactions between the polymer and graphene materials during solution processing can be clearly revealed. The ion‐transport experiments demonstrated in this work can be used as a set of tools for quick quality control and monitoring of production of graphene/polymer nanocomposites and nanoporous composites assembled with other 2D materials. Abstract : Ion‐transport experiments such as electrosorption (or supercapacitor) and membrane permeation are combined with traditional structural characterization techniques to gain in‐depth structural insights about graphene/polymer layered nanocomposites. This approach can reveal subtle characteristics of nanopore tortuosity and alignment that are otherwise undetected via traditional techniques. This method can be applied to other nanoporous structures.